Interdisciplinary Swiss consensus recommendations on staging and treatment of advanced prostate cancer (Swiss Medical Weekly, 2023)
The management of prostate cancer is undergoing rapid changes in all disease settings. Novel imaging tools for diagnosis have been introduced, and the treatment of high-risk localized, locally advanced and metastatic disease has changed considerably in recent years. From clinical and health-economic perspectives, a rational and optimal use of the available options is of the utmost importance. While international guidelines list relevant pivotal trials and give recommendations for a variety of clinical scenarios, there is much room for interpretation, and several important questions remain highly debated. The goal of developing a national consensus on the use of these novel diagnostic and therapeutic strategies in order to improve disease management and eventually patient outcomes has prompted a Swiss consensus meeting. Experts from several specialties, including urology, medical oncology, radiation oncology, pathology and nuclear medicine, discussed and voted on questions of the current most important areas of uncertainty, including the staging and treatment of high-risk localized disease, treatment of metastatic hormone-sensitive prostate cancer (mHSPC) and use of new options to treat metastatic castration-resistant prostate cancer (mCRPC).